Is Bowel Preparation Necessary Before kidney-Ureter-Bladder Radiography and Intravenous Urography? - Dadkhah, Farid; Safarinejad, Mohammad Reza; Amini, Erfan; Soleimani, Mohammad; Lashay, Ali Reza (Urology Journal, 2012)
PURPOSE: To assess whether bowel preparation prior to kidney-ureter-bladder (KUB) radiography and intravenous urography (IVU) are of value in improving visualization of the urinary system. MATERIALS AND METHODS: A total of 186 patients participated in this study. Thirty-nine patients with chronic constipation based on Rome III criteria and 147 patients with normal bowel habits were included. All the patients were randomly divided into two groups. Patients in group 1 received castor oil before imaging and had to eat or drink nothing after midnight. Patients in group 2 were allowed to eat and drink before the examination and received no bowel preparation. Kidney-ureter-bladder radiographies were obtained in all the patients and IVUs were indicated in 77 patients. To assess the image quality, radiographic images were divided into 5 anatomical regions and each region was scored from 0 to 3 based on obscurity of the images by the bowel gas or fecal residue. RESULTS: Mean total score for visualization of the urinary system on plain and contrast images did not differ significantly between the two groups (P = .253). However, patients with chronic constipation who received bowel preparation revealed a significantly better visualization score on plain images (P = .001). CONCLUSION: Bowel preparation prior to KUB and IVU does not improve the quality of the images in patients with normal bowel habits. However, a significantly better visualization of KUB was noted among patients with chronic constipation who had received bowel preparation.